Analisis Perbandingan Isi Tajuk Rencana Surat Kabar Harian Analisa dan Waspada Edisi 1-31 Agustus 2016 (Universitas Medan Area, 2017)
Daily Newspaper Analysis and Alert have the same marketing and news coverage area in their own city of course. So the two newspapers will always continue to compete in obtaining news. It also allows both of them to share the same news. It may be that both of them raise the same event but are written in different angles. The difference between the two newspapers is the content of the editorial, as the content of the editorial is an opinion written by the editor of the editor himself. So it is only natural that the content of the editorial differs from newspaper to newspaper, even though it raises the same problem. Through editorials, the editor can provide both criticism and suggestions to the government as well as those with an interest to the community. This is because an editorial contains information on issues that are going on in the community. Research on the differences in the content of the editorial because there are differences in newspaper tendencies. Therefore, to see this the researcher chose to use content analysis method. Using this method, the researcher can prove that Daily Analysis and Alert do have differences in published writing and viewed from the content of the editorial.